Environmental assessment of gooseberry cultivars developed in Chelyabinsk Province - A. A. Vasiliev; F. M. Gasymov; N. V. Glaz (Труды по прикладной ботанике, генетике и селекции, 2021)
The analysis of environmental plasticity and stability made it possible to identify adaptable gooseberry cultivars: ‘Avangard’ (CA = 1.77), ‘Vladil’ (CA = 1.58), ‘Grinchel’ (CA = 1.24), ‘Kovcheg’ (CA = 1.13) and ‘Arlekin’ (CA = 1.01). Cv. ‘Grinchel’, submitted for state trials in 2020, is an intensive-type cultivar (bi = 1.49), cvs. ‘Arlekin’ (bi = 1.03; Si2 = 4.1) and ‘Vladil’ (bi =1.03; Si2 = 1.0) are environmentally plastic and stable, while cvs. ‘Avangard’ (bi = 0.51) and ‘Kovcheg’ (bi = 0.53) belong to the neutral type. The advantages of these cultivars are their high productivity, large fruit size, dessert flavor, high winter hardiness, low thorniness, and increased resistance to American gooseberry mildew. High productivity in years with favorable and satisfactory growing conditions can be provided by the intensive-type cultivars ‘Stanichny’ (bi = 1.55) and ‘Kooperator’ (bi = 1.35) as well as the plastic but insufficiently stable cv. ‘Uralsky Izumrud’ (bi = 1.03; Si2= 5.3).